Research on Tax Avoidance and Anti-tax Avoidance of Data Asset Related transactions– Based on the Rerspective of Connected Party Transactions in China - He, Xiaosha (Innovative Applications of AI, 2024)
Due to the characteristics of data assets different from traditional elements, with the expansion of China’s data asset trading market scale and the increase of connected transactions, the existing tax collection and management system needs to be improved to prevent tax revenue loss. Through the elaboration of the concept and characteristics of data assets, this paper analyzes the types of group enterprises using data asset related transactions to avoid tax and the current anti-tax avoidance regulations of related transactions in China, points out the current anti-tax avoidance difficulties of data asset related transactions in China and puts forward policy improvement suggestions.